Arts Community Resilience in Malaysia during the Time of COVID-19: Five Arts Centre’s Open House Initiative - Ali Alasri; Simon Soon (Wacana Seni Journal of Arts Discourse, 2024)
The intrusion of COVID-19 in Malaysia had resulted in the disruption of many art projects for the whole year of 2020. Due to the country’s countermeasures to combat the disease’s ongoing spread, several art groups and art projects were facing mass postponements, cancellations, and uncertainty—arts communities were vulnerable to economic losses, social and environmental limitations during the volatile period. However, there were few art groups that managed to adapt their practices and work around the pandemic constraints they’ve encountered. Five Arts Centre arts collective was sampled and interviewed for this year-long study which looks at the preliminary impacts and responses of COVID-19 on the arts communities in Kuala Lumpur. The results indicate Malaysian arts communities were able to remain resilient against the pandemic mostly due to their social connectedness across the arts practitioners and institutions within the arts ecosystem. Added with their intuitive instrumentalisation of existing resources to meet the environmental limitations that the COVID-19 presented. The research findings are analysed through the utilisation of an adapted resilience framework to help explain the sampled art groups’ experiences through the pandemic period.